Evaluation of losses due to the rust on beans (Phaseolus vulgaris L.) in four sowing times in Cuba. - González, Miguel; García, Evelio (Agronomía Mesoamericana, 2016)
In the Velasco zone, Holguín province, Cuba, losses in yield due to the bean rust were valued on the varieties ICA- Pijao, Velasco Largo and Bonita 11 in four sowing times between 1987 and 1989. A randomized block design with three replicates was used. The considered treatments were the aforesaid three varieties of common bean, sprayed with fungicides and unprotected. The used chemical was oxycarboxin, sprayed five times at 0.75 kg a.i. 1 ha with a 10 days frecuency, beginning 15 days after sowing. It was concluded that bean rust might cause shortages in yield reaching 28-54%, 8-33% and 13-29% on the varieties ICA- Pijao, Velasco Largo and Bonita 11 respectively as well as a decrease on the average number of pods per plant and also the weight of the seeds.